Current concepts for the management of systemic lupus erythematosus in adults: a therapeutic challenge. Issue 924 (1st October 2002) - Ioannou, Y; Isenberg, D A
Abstract : Systemic lupus erythematosus (SLE) is a chronic, autoimmune rheumatic disease with many clinical presentations typically affecting women of childbearing age. The successful therapy of SLE depends upon treating both symptoms and the underlying inflammation. Both non-pharmacological as well as pharmacological therapies are invariably required. Non-pharmacological therapy includes avoiding over-exposure to sunlight with the use of adequate sunscreen protection, avoiding "live" vaccination if on immunosuppressive agents, adherence to a diet low in saturated fat and high in fish oil, stress avoidance, and smoking cessation. Pharmacological measures revolve around four main classes of drugs: non-steroidal anti-inflammatory drugs, antimalarials, corticosteroids, and cytotoxic agents. Cyclophosphamide and azathioprine are the two most commonly used cytotoxic agents and these in combination with corticosteroids need to be employed early if there is major organ involvement to prevent or minimise irreversible damage. The potential side effects of corticosteroids and cytotoxic agents need constant consideration. The rapid developments in biotechnology of recent years may soon lead to new and more specific therapies for patients with SLE.